2004
DOI: 10.1177/0091270004265647
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of an Orally Active Novel Camptothecin Analog, DRF‐1042, in Refractory Cancer Patients in a Phase I Dose Escalation Study

Abstract: The objective of this study was to characterize the maximum tolerated dose (MTD), dose-limiting toxicities (DLT), pharmacokinetics, and antitumor effects of DRF-1042, a novel camptothecin analog, in refractory solid tumor patients. DRF-1042 was given for 5 consecutive days for 2 weeks, repeated every 3 weeks at 1.5 to 270 mg/m(2). Adverse events were monitored following NCI-CTC. Pharmacokinetics of lactone and total forms were determined using validated high-performance liquid chromatography (HPLC) and noncomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…All patients were hospitalized for the duration of the treatment. The starting dose (81 mg/m 2 ) corresponded to 1 dose level lower than the MTD in humans 9,10 . DRF‐1042 was administered orally in the morning on an empty stomach to the first 3 patients for 5 consecutive days for 2 weeks every 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were hospitalized for the duration of the treatment. The starting dose (81 mg/m 2 ) corresponded to 1 dose level lower than the MTD in humans 9,10 . DRF‐1042 was administered orally in the morning on an empty stomach to the first 3 patients for 5 consecutive days for 2 weeks every 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 2 partial responses were documented in 1 patient each with osteosarcoma and breast carcinoma. Four patients also had disease stabilization 9,10 …”
mentioning
confidence: 95%
“…For example, 5‐propionyl and 5‐ethoxy derivatives bearing a hydroxy, methoxy, or fluoro group at the β‐position showed good antitumor activity. One of these analogs, DRF‐1042, is currently in phase II clinical trials . These findings prompted other studies to investigate the role of modification at the C‐5 position.…”
Section: Biological Activity Of Cpt and Related Derivativesmentioning
confidence: 99%
“…You et al 46 reported a series of 7-cycloalkylcamptothecin derivatives (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). As shown in Table III, many of the compounds exhibited IC 50 values in the low moicromolar-to-nanomolar level and were up to 40-fold more potent than 3, the reference compound.…”
Section: A and B Ring Modified Cpt Derivativesmentioning
confidence: 99%
See 1 more Smart Citation